What is the value of third‐line chemotherapy in advanced gastroesophageal cancer? A 5‐year retrospective analysis at a single center. Issue 1 (17th November 2019) - Lam, Justina Yick Ching; Choo, Su Pin; Tai, David Wai‐Meng; Tan, Iain Bee Huat; Tham, Chee Kian; Koo, Wen Hsin; Ong, Simon Yew Kuang; Ang, Soo Fan; Chua, Clarinda Wei Ling; Chong, Dawn Qingqing; Teo, Patrick Tze Hern; Lee, Christabel Jing Zhi; et al.
Abstract: Aim: The survival benefit of using a non‐cross resistant second‐line chemotherapy in the third‐line setting in metastatic gastroesophageal cancer is unproven. We evaluated the utility of third‐line chemotherapy in patients treated at a single institution. Methods: Between 2010 and 2014, efficacy and toxicity data of patients who received three or more lines of systemic therapies for metastatic gastroesophageal adenocarcinoma at the National Cancer Centre Singapore was retrospectively analyzed. Results: Thirty‐two (6%) patients received three or more lines of chemotherapy. The median age and ECOG performance status were 59 years (36–82) and 1 (0–2), respectively. Majority of patients (88%) had tumor located in the stomach and 13 patients (41%) had diffuse histology or poorly cohesive or signet ring cells. Four (12%) patients had HER2‐positive disease. Prior therapy was platinum (100%), fluoropyrimidine (97%), taxane (63%), irinotecan (28%), anthracycline (13%) and ramucirumab (3%). Third‐line therapy consisted of 24 (75%) monotherapy, 6 (19%) doublet, 1 (3%) triplet chemotherapy and 1 (3%) clinical trial. Monotherapy irinotecan (44%) was most common, followed by docetaxel (19%) and paclitaxel (9%). Of 22 patients evaluable for response, there was 1 (5%) partial response, 9 (41%) stable disease. Median overall survival was 18.3 weeks (4.3–65.1). Of 30 patients evaluable for toxicities, 17 (57%) experienced at least one grade 3 or 4 toxicities. Conclusion: The benefit of using non‐cross resistant second‐line regimens as third‐line chemotherapy was small with moderate toxicity. Newer agents such as nivolumab or TAS‐102 or clinical trial may be preferred.